The Influence of Attitude, Subjective Norm, Price Consciousness on Purchase Decision Through Purchase Intention in Green Products - Raden Roro Ruvita Oktaviani; Bernadetta Diansepti Maharani; Putri Dwi Cahyani (Journal of Economy, Accounting and Management Science (JEAMS), 2025)
This research aims to determine (1) the influence of Attitude on Purchase Intention (2) the influence of Subjective Norms on Purchase Intention (3) the influence of Price Consciousness on Purchase Intention (4) the influence of Purchase Intention on Purchase Decision. The sample in this research was 144 respondents from the people of Yogyakarta who had purchased environmentally friendly products. The data collection method uses a distributed questionnaire method and the sampling technique uses a purposive sampling technique. This research uses the Data Quality Test, Classical Assumption Test, Multiple Linear Regression Test, and Hypothesis Test. The research results show (1) there is no positive and significant influence on Attitude on Purchase Intention (2) there is a positive and significant influence on Subjective Norm on Purchase Intention (3) there is a positive and significant influence on Price Consciousness on Purchase Intention (4) there is a positive and significant influence on Purchase Intention on Purchase Decision.